Producing Pornographic Content from the Perspective of Islamic Criminal Law: A Study of the Decision of the Banda Aceh District Court Number 6/Pid.B/2026/PN.Bna - Fara Shuhada; Edi Yuhermansyah; T. Surya Reza (MAQASIDI: Jurnal Syariah dan Hukum, 2026)
This study aims to analyze the considerations of the panel of judges in Decision Number 6/Pid.B/2026/PN.Bna and examine the perspective of Islamic criminal law on the act of producing pornographic content. This study uses a normative juridical research method with a statutory approach and a case approach. The data used are in the form of primary, secondary, and tertiary legal materials which are analyzed qualitatively. The results of the study indicate that the regulation of the crime of pornography in Indonesian positive law is regulated in Law Number 44 of 2008 concerning Pornography and Law Number 1 of 2023 concerning the Criminal Code. In Decision Number 6/Pid.B/2026/PN.Bna, the panel of judges imposed a sentence based on Article 407 paragraph (1) of the Criminal Code in conjunction with Law Number 1 of 2026 with the consideration that the defendant's actions have fulfilled the elements of violating morality and were carried out intentionally. However, normatively the provisions in the Pornography Law should be used as Lex specialis. From an Islamic criminal law perspective, this act is prohibited because it violates the principles of maintaining honor and privacy as stipulated in the Qur'an, Surah Al-Isra', verse 32, Surah Al-Hujurat, verse 12, and the Hadith of Arba'in Nawawi, number 35. It falls under the category of ta'zir crimes. Therefore, both legal systems view this act as a violation of morality worthy of punishment.